1969
DOI: 10.1175/1520-0493(1969)097<0424:wvaafo>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Wind Variability as a Function of Time

Abstract: Kolmogorov's structure functions for longitudinal and transverse components of isotropic turbulence when combined vectorially provide a prediction that vector time variability of the horizontal wind should vary as the cube root of the lag period. Published wind variability data are examined and found to be generally consistent with this prediction for time periods of up to 4 t o 6 hr and, when representative of the hemispheric mean excluding the tropical stratosphere, may be consistent with such a prediction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1969
1969
1989
1989

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Their observations were taken with special smallsample fast-response equipment a t elevations of 7.5 cm to 153 m. Accepting their reports as validating equation 8for evaluating e over equivalent distances (;t) comparable to the elevation of the observation point, its validity for greater lag times (equivalent distances) depends only on the validity of (6). I n a companion study, published wind variability data were found to be generally consistent with (6) for lag periods up to 6 hr (Ellsaesser, 1969).…”
Section: Validity Argumentssupporting
confidence: 53%
“…Their observations were taken with special smallsample fast-response equipment a t elevations of 7.5 cm to 153 m. Accepting their reports as validating equation 8for evaluating e over equivalent distances (;t) comparable to the elevation of the observation point, its validity for greater lag times (equivalent distances) depends only on the validity of (6). I n a companion study, published wind variability data were found to be generally consistent with (6) for lag periods up to 6 hr (Ellsaesser, 1969).…”
Section: Validity Argumentssupporting
confidence: 53%